Thromboplastin as a Clotting Factor - Quick, A. J (Thrombosis and Haemostasis, 1971)
The clotting activity of platelets can be sensitively measured by the prothrombin consumption time using normal platelet-depleted plasma as the assay medium. Such plasma when clotted in a glass tube shows no demonstrable consumption of prothrombin but as platelets are added in increasing amounts, the utilization of prothrombin is increased in an approximately straight-line proportion. Similar results are obtained when certain agents such as the Bell-Alton reagent, Inosithin and hemolysate, all of which have a high concentration of phospholipids and are employed in the thromboplastin generation test as platelet substitutes, were assayed by the prothrombin consumption test. Both Inosithin and the Bell-Alton reagent fail to cause significant consumption of prothrombin when the plasma is clotted in silicone-coated tubes, thereby demonstrating the need of a contact factor which is probably thrombin. Since Inosithin which is of plant origin functions efficiently as a platelet substitute in the thromboplastin generation test and in the prothrombin consumption assay test, it presents the probability that the clotting factor in platelets could be of exogenous origin. Its release from platelets requires the action of thrombin.